NOX4-reactive oxygen species axis: critical regulators of bone health and metabolism - Dzubanova, Martina; Bond, Jacob M.; Craige, Siobhan M.; Tencerova, Michaela (Frontiers in Cell and Developmental Biology, 2024)
Bone marrow stromal cells (BMSCs) play a significant role in bone metabolism as they can differentiate into osteoblasts, bone marrow adipocytes (BMAds), and chondrocytes. BMSCs chronically exposed to nutrient overload undergo adipogenic programming, resulting in bone marrow adipose tissue (BMAT) formation. BMAT is a fat depot transcriptionally, metabolically, and morphologically distinct from peripheral adipose depots.Reactive oxygen species (ROS) are elevated in obesity and serve as important signals directing BMSC fate. ROS produced by the NADPH oxidase (NOX) family of enzymes, such as NOX4, may be responsible for driving BMSC adipogenesis at the expense of osteogenic differentiation. The dual nature of ROS as both cellular signaling mediators and contributors to oxidative stress complicates their effects on bone metabolism. This review discusses the complex interplay between ROS and BMSC differentiation in the context of metabolic bone diseases.Special attention is paid to the role of NOX4-ROS in regulating cellular processes within the bone marrow microenvironment and potential target in metabolic bone diseases.